MODAL SOSIAL DAN KEBERLANJUTAN USAHATANI MENDONG - Tenten Tedjaningsih; Dedi Sufyadi (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Capacity of farmer can not take away from potencial power themselves, such as individual potencial and group potencial.  Individual potencial are such as fisic and intellectual, while group potencial are such as cooperation ability and trust.  Cooperation ability is ability to rule out personal make responsibility and both depend on group degree of various norms and values.  Ability of group is called by social capital.  Method of this research is survei method to the farmer of mendong in Kamulyan Manonjaya Tasikmalaya Regency.  Sample responden was taken by simple random sampling.  Data was analyzed by descriptive and Konkordans Kendal W analysis to know relationship between social capital and sustainability of business.  The result of this research is overall social capital that collaboration network, reciprocity, trust, norm, cooperation value and proactive were included the high category.  Sustainability of mendong farming was seen from ability of production facilities, capital, marketing, organize group and obtain information and technology were include as good enough.  There was correlation between social capital and sustainability of mendong farm. Power of social capital can be done together by power of human resource through education,because it was means of interacting and developed of positive norms was professionalism of mendong farm.